Avaliação do potencial antinociceptivo do polissacarídeo obtido a partir da levedura Rhodotorulaoryzicola - Ferraz, Flávia Menezes (2017)
The yeasts are constituted by different macromolecules, among them the polysaccharides. The pharmaceutical industry has used polysaccharides as an important raw material for the development of new drugs, since they present several pharmacological activities, such as antitumor, antioxidant, anti-inflammatory, antinociceptive and immunomodulatory activities. The yeast Rhodotorulaoryzicola, present in the semi-arid region of Bahia, deserves to be highlighted, since it is still little explored in relation to its biotechnological potential. The present study analyzed the possible antinociceptive effect of the polysaccharide obtained from yeast R. oryzicola, through pain models in mice. This study was approved by the Commission of Ethics in the Use of Animals of the State University of Feira de Santana (06/2013). Intraperitoneal administration of the polysaccharide (9 and 27 mg/kg) showed dose-dependent inhibition of the number of abdominal writhes induced by acetic acid. In the formalin test, pre-treatment with the polysaccharide (27 mg/kg) showed antinociceptive activity only in the second phase of the test. It was observed that the polysaccharide (9, 27 and 81 mg/kg) altered the thermal stimulus response threshold used in the tail withdrawal test, thus indicating a possible central action presence. In the model of mechanical hypernociception induced by CFA, pre-treatment with the polysaccharide (27 and 81 mg/kg) inhibited CFA-induced hypernociception. Ratifying the specificity of the antinociceptive action, the polysaccharide (27 mg/kg) did not change the motor behavior of the animals in the rota rod and open field models. The structural characterization showed mannosyl residues involved in α-3,6-type binding, suggesting that the sample is amannan. The results demonstrate that the polysaccharide has an efficient antinociceptive activity, indicating its development for the treatment of inflammatory pain conditions